PEMBUKTIAN UNSUR KECAKAPAN DAN KEWENANGAN PARA PIHAK DALAM TRANSAKSI BISNIS E-COMMERCE - Yonani Yonani (Fakultas Hukum Universitas IBA Palembang, 2020)
ABSTRACT The existence of business transactions through the internet brings different new implications, where business activities are initially carried out in person and face-to-face between parties, but with the existence of the internet business activities can be carried out electronically, or better known as electronic -commerce and abbreviated as e-commerce. Recognition of electronic contracts as a form of agreement in the Indonesian Civil Code (KUH Perdata) is still a complicated problem. Article 1313 of the Civil Code concerning the definition of the agreement does not determine that an agreement must be made in writing. The validity of electronic contracts as a form of agreement in the Indonesian Civil Code is still a complicated problem. Article 1313 of the Civil Code concerning the definition of an agreement is an act in which one or more people attach themselves to one or more other people. If referring to this definition, an electronic contract can be considered as a form of agreement that complies with the provisions of Article 1313 of the Civil Code